Soil microbiota influences clubroot disease by modulating Plasmodiophora brassicae and Brassica napus transcriptomes. Issue 5 (19th July 2020) - Daval, Stéphanie; Gazengel, Kévin; Belcour, Arnaud; Linglin, Juliette; Guillerm‐Erckelboudt, Anne‐Yvonne; Sarniguet, Alain; Manzanares‐Dauleux, Maria J.; Lebreton, Lionel; Mougel, Christophe
Summary: The contribution of surrounding plant microbiota to disease development has led to the 'pathobiome' concept, which represents the interaction between the pathogen, the host plant and the associated biotic microbial community, resulting or not in plant disease. The aim herein is to understand how the soil microbial environment may influence the functions of a pathogen and its pathogenesis, and the molecular response of the plant to the infection, with a dual‐RNAseq transcriptomics approach. We address this question using Brassica napus and Plasmodiophora brassicae, the pathogen responsible for clubroot. A time‐course experiment was conducted to study interactions between P. brassicae, two B. napus genotypes and three soils harbouring high, medium or low microbiota diversities and levels of richness. The soil microbial diversity levels had an impact on disease development (symptom levels and pathogen quantity). The P. brassicae and B. napus transcriptional patterns were modulated by these microbial diversities, these modulations being dependent on the host genotype plant and the kinetic time. The functional analysis of gene expressions allowed the identification of pathogen and plant host functions potentially involved in the change of plant disease level, such as pathogenicity‐related genes (NUDIX effector) in P. brassicae and plant defence‐related genes (glucosinolate metabolism) in B. napus . Abstract : The objective was to further the understanding of the complex interaction between the soil microbiota, a plant pathogen and the host plant. The effect of different soil microbial diversities on the level of disease and on the transcriptomes of the interacting pathogen and host plant was studied.